Chlamydia trachomatis in a girl suspected of sexual abuse in the city of Córdoba, Argentina - Kiguen, Ana Ximena (2014)
Chlamydia trachomatis (C.tr) infections are the most prevalent bacterial sexually transmitted infections worldwide. They are often asymptomatic and therefore underdiagnosed as there is no routine screening surveillance. This case supports the possibility of sexual abuse as a route of transmission of C.tr. It is well known that nearly one third of sexually assaulted children are at risk for infection by a sexually transmitted agent. This is why in cases of sexual abuse, it is standardized that C.tr positive results by Nucleic Acid Amplification Techniques (NAATs) should be confirmed looking for another C.tr target; for this reason, we used a Polimerase Chain Reaction (PCR) directed to cryptic plasmid of C.tr. Confirmation was specified by the use of another PCR with a different genetic target (ompA) and sequencing. We concluded that our patient’s oral lesions were probably originated by her father’s sexual abuse.